2002
DOI: 10.1128/iai.70.6.2787-2795.2002
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Genes Induced during Infection of Human Macrophages

Abstract: We identified Mycobacterium tuberculosis genes preferentially expressed during infection of human macrophages using a promoter trap adapted for this pathogen. inhA encodes an enoyl-acyl carrier protein reductase that is required for mycolic acid biosynthesis ( Virulence genes are generally defined as genes that are necessary for survival of the pathogen in a host and are involved in pathogenicity but are not necessary for growth in culture medium. Several virulence genes of Mycobacterium tuberculosis have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
104
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(107 citation statements)
references
References 35 publications
3
104
0
Order By: Relevance
“…To discount the possibility that the presence of Eis in the macrophage cytoplasm may be due to intracellular lysis of phagocytosed bacteria, the cytoplasmic fraction was probed by Western blot analysis for the presence of the 16 kDa alpha crystallin protein (Acr) at 48 h after infection. Acr is a mycobacterial protein encoded by hspX that is upregulated in M. tuberculosis during infection of macrophages and is known not to be secreted from the bacteria (Dubnau et al, 2002). Acr was not detected in the cytoplasmic fraction of macrophages infected with M. tuberculosis by Western blot analysis.…”
Section: Western Blot Analysis Of the Cytoplasm Of Infected Macrophagmentioning
confidence: 99%
“…To discount the possibility that the presence of Eis in the macrophage cytoplasm may be due to intracellular lysis of phagocytosed bacteria, the cytoplasmic fraction was probed by Western blot analysis for the presence of the 16 kDa alpha crystallin protein (Acr) at 48 h after infection. Acr is a mycobacterial protein encoded by hspX that is upregulated in M. tuberculosis during infection of macrophages and is known not to be secreted from the bacteria (Dubnau et al, 2002). Acr was not detected in the cytoplasmic fraction of macrophages infected with M. tuberculosis by Western blot analysis.…”
Section: Western Blot Analysis Of the Cytoplasm Of Infected Macrophagmentioning
confidence: 99%
“…The glyoxylate pathway enables bacteria to grow on acetate. Interestingly, two genes, aceA and aceB, of which the corresponding gene products catalyze subsequent steps of the glyoxylate pathway, were isolated with IVET from the animal pathogens Mycobacterium tuberculosis (56) and Yersinia enterocolitica (300), respectively. An independent SCOTS experiment equally showed that Mycobacterium tuberculosis cells contain more aceA transcript during macrophage infection (86).…”
Section: Genes Involved In Central Intracellular Metabolismmentioning
confidence: 99%
“…Several authors adapted the auxotrophy-based selection strategy and used other essential metabolic genes (Table 1): panB, involved in pantothenate biosynthesis (218); dapB or asd, involved in diaminopimelate biosynthesis (63,78,95,224,245); metXW (159) or trpEG (26), necessary for methionine and tryptophan biosynthesis, respectively; inhA, required for mycolic acid biosynthesis (56); pyrB or thyA, necessary for de novo biosynthesis of pyrimidine nucleotides (140,156); galU, involved in galactose metabolism (133); or ribBAH, involved in riboflavin biosynthesis (76). IVET was also applied to study infection of mice by the pathogenic fungus Histoplasma capsu-latum.…”
Section: Selection Strategies In Ivetmentioning
confidence: 99%
“…However, this variability can not be extended to all pe/ppe family members since some are in fact conserved across strains and species (Cubillos-Ruiz et al, 2008). It has then been suggested that the PPE proteins may play a role in the virulence of Mtb (Rindi et al, 1999;Li et al, 2005), in the maintenance of bacterial growth in macrophages (Camacho et al,1999;Dubnau et al, 2002;Hou et al, 2002;Li et al, 2005;Sassetti et al, 2003) and in the regulation of bacterial iron starvation and oxidative stress responses (Rodriguez at al., 1999;Rodriguez at al., 2002). In addition, PPE might be a target for the protective immune response in experimental mouse models (Skeiky et al, 2000).…”
Section: Characterization Of P27-ppe36 Proteinmentioning
confidence: 99%